PCNN Model Automatic Linking Strength Determination Based on Geometric Moments in Image Fusion. Issue 1 (March 2014) - Shu, Zhibiao
In order to obtain a clear image that contains all relevant objects in all area, this paper proposes a new image fusion algorithm. The proposed method can adaptively determine the linking strengths of PCNN based on the regional image moment invariants. Compared with the traditional methods, the results of experiments show that the new algorithm enhances the fusion image information, effectively retains the source image edges and detail information. The effect of fusion and quantifying indicators are fairly good.